1988
DOI: 10.1007/bf02371201
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic response to sodium chloride salinity of four major olive cultivars (Olea europea L.)

Abstract: The relative tolerance to NaC1 of the olive cultivars 'Amphissis', 'Chondrolia Chalkidikis', 'Koroneiki' and 'Megaritiki' was studied in a nutrient-solution pot experiment. Three-year-old plants produced from cuttings were transplanted to sand-perlite (1/1) culture and irrigated with 1/2 strength Hoagland solution containing NaC1 at various levels, i.e. O, 15, 30, 45, 60 and 80meql -l in the first and 0, 30, 60, 90, 120 and 150meq 1 -I in the second experiment. The overall results indicate that NaCI applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
6

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 21 publications
5
35
0
6
Order By: Relevance
“…Irrigation water with 8 g/L NaCl has been found to be the tolerance limit for olive trees (23). Recently (31), it has been shown that three year old olive plants did not suffer salt stress at NaCl concentrations lower than 80 mM during a 90-day culture period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrigation water with 8 g/L NaCl has been found to be the tolerance limit for olive trees (23). Recently (31), it has been shown that three year old olive plants did not suffer salt stress at NaCl concentrations lower than 80 mM during a 90-day culture period.…”
Section: Introductionmentioning
confidence: 99%
“…Olive is considered as having a medium tolerance to salt (14,23,31). with young olive plants tolerating a SAR of 18 in the growing medium, producing new growth at leaf Na levels of up to 0.4% (1).…”
Section: Introductionmentioning
confidence: 99%
“…The significant decrease of leaf chlorophyll concentration in the CAB-6P explants treated with CaCl 2 (30 and 60 mM) or 60 mM NaCl could be probably ascribed to the toxic effect of the high Cl -concentration (4.2-5.6% DW). Furthermore, high Cl -concentrations could be the cause for the growth reduction of plants (Therios and Misopolinos 1988). In the present study, there was a decline in growth parameters of CAB-6P under 30 or 60 mM CaCl 2 .…”
Section: Discussionmentioning
confidence: 86%
“…Hence, Cl -concentration could be the cause for the growth decrease (Therios and Misopolinos 1988). Usually, increase of NaCl concentration in the growth medium decreases dry mass and shoot length.…”
Section: Discussionmentioning
confidence: 99%
“…Salinity poses serious threats to fruit production (Cresti et al, 1994) by negatively affecting leaf morphology (Therios, 2009) and photosynthesis (Loreto et al, 2003;Tabatabaei, 2006) as well as shoot growth (Tattini et al, 1992;Klein et al, 1994). The tolerance of olive to NaCl is supposed to be intermediate (Rugini and Fedeli 1990), although, extensive genetic diversity is found in olive germplasm against abiotic stresses (Therios et al, 1988;Chartzoulakis, 2005). Certain physiological mechanisms attribute tolerance through retention of Na + and Cl -by root and stem, Na + exclusion due to influx of K + and by compartmentalization of toxic Na + and Cl -into vacuole.…”
Section: Transcriptome Changes In Response To Salinitymentioning
confidence: 99%